The Relationship between Eye-Hand Coordination and Concentration on Shooting Results of UKM Petanque UIR Athletes: Hubungan Kordinasi Mata Tangan Dan Konsentrasi Pada Hasil Shooting Atlet UKM Petanque UIR - Khoirul Ashari; Mimi Yulianti (Jurnal Olahraga dan Kesehatan (ORKES), 2022)
Petanque sport is a sport that has 11 competition numbers, such as: single man, single woman, double man, double woman, double mix, triple man, triple woman, triple mix 1 woman 2 man, triple mix 2 woman 1 man, shooting men, shooting woman, team. In the game of petanque there are two throwing techniques, is called pointing and shooting. Shooting is the most important part of the petanque game. The success of shooting must also be considered, namely: ball grip (technique in holding bosi), body position towards the target (body alignment with the target), static balance of the legs, low body position and leaning forward, release the ball (release the ball) follow through. The purpose of this research was to determine the relationship between eye-hand coordination and concentration on the shooting results of UKM Petanque UIR athletes. The type of this research is multiple correlation. The population and sample in this research were athletes from UKM Petanque UIR, amounting to 16 people. The research instrument used was a test of hand eye coordination, a concentration test and a shoting petanque test. The data analysis technique used is the multiple correlation value test. Based on the results of the research that has been done, a conclusion can be drawn as follows (1). There is a relationship between eye-hand coordination and the shooting results of UKM Petanque UIR athletes with a value of tcount = 3.61 > ttable = 3.61, (2). There is a relationship between concentration and the shooting results of UKM Petanque UIR athletes with a value of tcount = 2.68 > ttable = 1.753, (3) There is a relationship between eye-hand coordination and concentration with the shooting results of UKM Petanque UIR athletes with a value of tcount = 3.76 > ttable = 1.753.